Reconfigurable Threshold Logic Gates using memristive devices - Thanh Tran; Rothenbuhler, A.; Smith, E. H. B.; Saxena, V.; Campbell, K. A. (2012 IEEE Subthreshold Microelectronics Conference, 2012)
We present our early design exploration of reconfigurable Threshold Logic Gates (TLG) implemented using Silver-chalcogenide memristive devices combined with CMOS circuits. A variety of linearly separable logic functions including AND, OR, NAND, NOR have been realized in a Matlab-Simulink/Cadence co-simulation using a single-layer TLG. The functionality can be changed between these operations by reprogramming the resistance of the memristive devices.